Restricted ability of group B streptococcal C5a-ase to inactivate C5a prepared from different animal species. - Bohnsack, J F (1993)
Most strains of group B streptococci (GBS) elaborate a cell surface-associated enzyme that rapidly inactivates the human complement-derived chemoattractants C5a and C5adesarg by cleaving the His-Lys bond at positions 67 and 68 in the C5a molecule. We have suggested that rapid inactivation of C5a and C5adesarg by this enzyme, called C5a-ase, can hinder the inflammatory response at sites of GBS infection. We tested the ability of GBS C5a-ase to inactivate C5a preparations from various animal species to determine the proper species for studying the role of GBS C5a-ase in the pathogenesis of GBS infections. Exposure of C5a preparations from humans, monkeys, and cows to GBS caused inhibition of C5a functional activity as measured by the ability of C5a to stimulate human polymorphonuclear leukocyte (PMN) adherence and human PMN chemotaxis. Bovine PMN chemotaxis to bovine C5a was also abolished after exposure of bovine C5a to GBS. In contrast, mouse, rat, guinea pig, rabbit, pig, and sheep C5a preparations retained full functional activity after exposure to GBS as measured by chemotaxis of human PMNs, PMNs from the same animal species, or both. These data suggest that there are structural differences between C5a proteins from different species which alter their susceptibility to GBS C5a-ase and indicate that most commonly used animal models of human GBS infection are inadequate for detection of a contribution of GBS C5a-ase to GBS virulence.